Predicting beta diversity of terrestrial and aquatic beetles using ecogeographical variables: insights from the replacement and richness difference components. (4th December 2018) - Heino, Jani; Alahuhta, Janne; Fattorini, Simone; Schmera, Dénes
Abstract: Aim: We examined the responses of the beta diversity of aquatic and terrestrial beetles to ecogeographical variables, including climate, land cover and land use, across Northern Europe. Location: Northern Europe (Denmark, Sweden, Norway and Finland). Methods: Information on the occurrence of ground beetles and diving beetles across Northern European biogeographical provinces was collated from literature sources. Beta diversity was examined using Jaccard dissimilarity coefficient as well as its replacement and richness difference components. Each of the three dissimilarity matrices (responses) was modelled using various ecogeographical variables (predictors) by generalized dissimilarity modelling (GDM). Results: The magnitude of total beta diversity was relatively similar between ground beetles and diving beetles, but the richness difference component contributed more than the replacement component to total beta diversity in ground beetles, whereas the opposite was true for diving beetles. The predictor variables most influential in GDM in accounting for spatial variation in beta diversity varied between the two beetle groups as well as between the replacement and richness difference components. In general, the richness difference component of ground beetles responded strongly to latitude and associated climatic variables, whereas the replacement component of diving beetles varied strongly along the same geographical gradient. Main conclusions: Our findings suggest that the study of the determinants of biodiversity patterns benefits from the partitioning of beta diversity into different components and from comparing terrestrial and aquatic groups. For example, our findings suggest that the strong climatic and land use‐related gradients in beta diversity have important implications for predicting and mitigating the effect of ongoing global change on the composition of regional biotas.